2018
DOI: 10.14196/mjiri.32.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D optimization on quality of life of patients with fibromyalgia: A randomized controlled trial

Abstract: Background: Numerous studies have been conducted to evaluate the frequency of hypovitaminosis D in patients with fibromyalgia syndrome (FMS) and its association with FMS symptoms. This study aimed at assessing the effect of hypovitaminosis D on the symptoms and quality of life of patients with fibromyalgia. Methods: A total of 74 FMS patients with hypovitaminosis D were randomly assigned into group A (Trazodone 25 mg at bedtime + vitamin D 50 000 IU weekly) and group B (Trazodone 25 mg at bedtime + placebo). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 26 publications
2
39
0
3
Order By: Relevance
“…After 8 weeks of intervention, the treated group showed a significant improvement in FM scores, in contrast to the placebo group [25]. Subsequently, other studies were performed to evaluate the effect of vitamin D supplementation in FM patients [26][27][28][29][30][31]. Although in a limited sample of participants, all of these studies reported a beneficial effect of vitamin D supplementation.…”
Section: Vitamin Dmentioning
confidence: 99%
“…After 8 weeks of intervention, the treated group showed a significant improvement in FM scores, in contrast to the placebo group [25]. Subsequently, other studies were performed to evaluate the effect of vitamin D supplementation in FM patients [26][27][28][29][30][31]. Although in a limited sample of participants, all of these studies reported a beneficial effect of vitamin D supplementation.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Another randomized control trial concluded that vitamin D supplementation was beneficial in reducing pain in FM. A combination of vitamin D supplementation and an anti-depressant showed further improvement in physical and psychological symptoms [ 117 ]. Additional studies have also found vitamin D supplementation may provide significant relief of FM pain symptoms in patients with preexisting vitamin D deficiency [ 118 120 ].…”
Section: Methodsmentioning
confidence: 99%
“…The connection between vitamin D and FM has been widely studied [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. However, the relationship between vitamin D deficiency and FM is controversial among literature.…”
Section: Vitamin D In the Treatment Of Fibromyalgiamentioning
confidence: 99%
“…Estudos recentes demonstram que não há consenso sobre a relação entre FB e vitamina D, em particular a relação causa-efeito (Ellis, Kelly, Shurlock, & Hepburn, 2018). No entanto, o tratamento com vitamina D demonstrou ser eficaz na melhoria de certos sintomas da FB (Martins et al, 2020),(de Carvalho et al, 2018 como a percepção da dor e a hipersensibilidade musculo esquelética e, ainda, existem evidências que em pacientes com FB com redução dos níveis séricos de vitamina D (20.1 to 29 ng/mL como insuficiência e < 20 ng/mL como deficiência), uma combinação de suplementos desta vitamina e um antidepressivo convencional, como a trazodona, pode melhorar significativamente os sintomas físicos e psicológicos dos pacientes afetados (Mirzaei et al, 2018).…”
Section: -Hidroxivitamina Dunclassified